2018
DOI: 10.1148/radiol.2017170347
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Intrathoracic Biopsy and Repeat Biopsy for Evaluation of Programmed Cell Death Ligand–1 Expression for Immunotherapy in Non–Small Cell Lung Cancer

Abstract: Purpose To determine feasibility and safety of biopsy and repeat biopsy for assessment of programmed cell death ligand-1 (PD-L1) status. Materials and Methods This retrospective analysis reviewed 101 patients who underwent transthoracic core needle biopsy for the KEYNOTE-001 (MK-3475) clinical trial of pembrolizumab, an antiprogrammed cell death-1 therapy for non-small cell lung cancer, from May 2012 to September 2014. Sixty-one male patients (mean age, 66.1 years; range 36-83 years) and 40 female patients (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Although most published studies mention a failure rate, it is not always defined with this very precise criterion. Generally, however, although the failure rate is often higher for cytology specimens than the larger types of histology specimens, such as core biopsies, this is not the case between cytology specimens and smaller biopsy specimens, such as endoscopic bronchial biopsies . With these latter specimens, the failure rate is usually approximately 10%, a figure borne out by the current study, in which 10 of 60 pairs of specimens originally included could not be assessed because one or both specimens of a pair were inadequate.…”
Section: Discussionmentioning
confidence: 69%
“…Although most published studies mention a failure rate, it is not always defined with this very precise criterion. Generally, however, although the failure rate is often higher for cytology specimens than the larger types of histology specimens, such as core biopsies, this is not the case between cytology specimens and smaller biopsy specimens, such as endoscopic bronchial biopsies . With these latter specimens, the failure rate is usually approximately 10%, a figure borne out by the current study, in which 10 of 60 pairs of specimens originally included could not be assessed because one or both specimens of a pair were inadequate.…”
Section: Discussionmentioning
confidence: 69%
“…The 20.0% pneumothorax rate of our study are also lower than 23% from the study by Tsai et al . that assessed the feasibility and safety of CT‐guided biopsy for evaluation of PD‐L1 . In their study, in which an average of eight cores was obtained for evaluation of PD‐L1, 5 out of 25 patients who developed pneumothorax required intervention, whereas in our study with an average acquisition of five cores, none required intervention.…”
Section: Discussionmentioning
confidence: 64%
“…The same study mentioned above has shown that at least four cores are needed to reach an optimal correlation with the whole tumor for PD‐L1 status . Another study evaluating the feasibility of CT‐guided biopsy for evaluation of PD‐L1 status has acquired average of eight cores exclusively for the analysis of PD‐L1 status . Greater number of cores and lower gauge needles do result in greater amount of tumor tissue, and intuitively, having a larger amount of tissue is advantageous for undergoing various molecular studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, many other data underlined reliability of core needle biopsy (CNB) for lung cancer molecular profiling, even if some reports documented a slightly higher rate of complications [11][12][13]. More recently, both FNA cytology and CNB have been reported to be accurate, feasible and safe procedures for PD-L1 testing both retrospectively and in prospective studies [14][15][16]. It should be underlined that few data are known on the molecular features which characterize neoplastic lesions presenting as NSN, and poor information are available regarding the specific pattern of tumour presentation and growth as well as the diagnostic accuracy of different bioptic approaches in these settings.…”
mentioning
confidence: 99%